Comparative analysis of carbonized hybrid briquettes produced from cassava peel and sawdust for cooking application - Ajagbe, Charles Adesola; Zainuddin, Mohamad Faiz; Abd Manaf, Latifah; Nik Ab Rahim, Nik Nor Rahimah; Anguruwa, Gloria Titi (Universiti Putra Malaysia Press, 2025)
The increasing use of biomass residues in briquette forms is not just for disposal problems but provides alternatives to fossil fuel and fuelwood. This research concentrated on assessing the effectiveness of the briquettes when used for cooking. The briquettes were prepared from carbonized materials: 100% Cassava peels (CP), 100% Sawdust (SD) of Gmelina arborea and their hybrid (MIX1-75:25, MIX2-50:50, and MIX3-25:75) with starch binder in percentage (5% and 10%) by weight at varying resident time of 10, 20, and 30 minutes. ANOVA was utilized to evaluate the significance at p<0.05. The produced briquettes were oven-dried and subjected to mechanical, boiling test, and fuel performance tests to evaluate their suitability as domestic fuel. The result shows that shatter index ranged between 46.81%–95.54%, compressive strength ranged from 0.12–0.26 N/mm2. Briquette’s thermal efficiency with good flame was within the range of 24.27%–55.55%. However, the average burning rate of all the briquette types was between 0.39 to 0.85 kg/hr, while the average specific fuel consumption ranged from 0.08 to 0.14 kg/l. The briquette took 15 minutes to boil water from 96.9°C to 97. 9°C.The comprehensive briquette test reveals that cassava peel exhibits the highest capacity for handling, while hybrid briquettes MIX1 and MIX3 demonstrate commendable fuel performance. It was noted that the binder ratio, type of biomass material, and residence time significantly impact the properties of the briquettes.